EFFECT OF SALIVARY GLAND EXTRACT OF ARIOPHANTA PULMONATA ON ANGIOGENESIS OF TERTIARY VITELLINE VEINS IN CHICK EMBRYO - SARITA PATIL; G. R. GONJARI (The Bioscan, 2009)
Angiogenesis is the formation of new blood vessels from existing vessels. Natural inhibitor blocking the formation of new blood vessels is a promising anti cancer strategy or even in wound healing process. Chorioallantoic membrane (CAM) is well vascularized and used to study as in vivo model of angiogenesis. In the present investigation effect of salivary gland, alcohol extract of Ariophanta pulmonata on angiogenesis especially tertiary vitelline veins was undertaken. Fertilized eggs of Gallus gallus were incubated at 380 C and 70% relative humidity. In the embryos of 48, 55, 66, 72, 88 and 96 hrs CAM was exposed to 1 mg/ml salivary gland extract and were further incubated up to 144 hrs and CAM was studied. Results of the present study indicate significant inhibitory effect of the salivary gland extract on the number and area of tertiary vitelline veins (TVV). The maximum inhibition in number and area of TVV was found when the embryos were treated at 48 hrs and showed 70.70% and 80.32% depletion in the number and area of TVV respectively. Inhibition of angiogenesis was highly significant at 48, 55 and 66 hrs as compared to 72, 88, 96 hrs of incubated chick embryos. The antiangiogenic role of complex carbohydrates is discussed.